Case report: A hybrid open and endovascular approach for repairing a life-threatening innominate artery dissection using the simultaneous kissing stent technique - Kuo, Chu-Hsuan; Yang, Shun-Tai; Lu, Yueh-Hsun; Lu, Yu-Chun; Su, I-Chang (Frontiers in Neurology, 2023)
Managing acute innominate artery (IA) dissection associated with severe stenosis is challenging due to its rarity, possible complex dissection patterns, and compromised blood flow to the brain and upper extremities. This report describes our treatment strategy for this challenging disease using the kissing stent technique. A 61-year-old man had worsening of an acute IA dissection secondary to an extension of a treated aortic dissection. Four possible treatment strategies for kissing stent placement were proposed based on different approaches (open surgical or endovascular) and accesses (trans-femoral, trans-brachial, or trans-carotid access). We chose to place two stents simultaneously via a percutaneous retrograde endovascular approach through the right brachial artery and a combined open surgical distal clamping of the common carotid artery with a retrograde endovascular approach through the carotid artery. This hybrid approach strategy highlights the three key points for maintaining safety and efficacy: (1) good guiding catheter support is obtainable through retrograde, rather than antegrade, access to the lesion, (2) concomitant cerebral and upper extremity reperfusion is guaranteed by placing kissing stents into the IA, and (3) peri-procedural cerebral emboli are prevented by surgical exposure of the common carotid artery with distal clamping.